PENGARUH INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN SOMETHINC DI SURABAYA DIMEDIASI OLEH BRAND IMAGE - Romauli Nainggolan; Yasinta, Komang Lola (Universitas Ciputra Surabaya, 2023)
During the pandemic, the cosmetic industry in Indonesia has become one of the most profitable industries (Rizaty, 2021). The growth of the cosmetic industry has led to the emergence of continuous competitors, making it important to develop marketing strategies and possess knowledge about the factors that influence purchasing decisions in order to maintain a position amidst fierce competition. In a pre-survey conducted with 30 respondents aged between 17 and 50 years, it was found that influencer marketing and brand image are factors that influence the purchasing decisions of Somethinc products. Therefore, the purpose of this study is to determine the influence of influencer marketing (X) on the purchasing decisions (Y) of Somethinc products in Surabaya, with brand image (Z) as a mediating variable. The research method used in this study is SEM-PLS (Structural Equation Modelling-Partial Least Square), with Smart PLS as the analysis tool. The data used in this study are primary data collected through online questionnaires distributed via Google Form to 160 respondents. The results of this study indicate a significant influence of influencer marketing on brand image, as well as a significant influence of brand image on purchasing decisions. Furthermore, it was also found that brand image mediates the relationship between influencer marketing and purchasing decisions.